Review of sedimentary basin evolution in Cambodia based on tectonic setting and logical information - Sio, Sreymean; Or, Chanmoly; Eng, Chandoeun; Pech, Sopheap; Sreu, Tola (Berita Sedimentologi, 2023)
The paper aims to synthesize the evolution of sedimentary basins in Cambodia based on a comprehensive information on tectonic setting and existing database of their formation and sedimentation. The study includes a review on tectonic setting of Indochina, the formation of sedimentary basins around Cambodia, and the accessible data on sedimentary basins in Cambodia. Indochina, as well as Cambodia, had been influenced by the collision of three different plates or terranes such as the South China, Sibumasu-Sukhothai, and Paleo-Pacific that are associated with the evolution of Paleozoic-Mesozoic Basins namely Khorat and Kampong Som Basins. These two oldest basins, are interpreted as a Paleozoic – Mesozoic foreland basin that initially formed due to rifting during the Late Carboniferous to Late Permian, and later basin inversion and erosion took place due to the Mesozoic to earliest Cenozoic uplift. Then, Cambodia was affected by Tertiary strike-slip fault movements that also influenced the formation of Tonle Sap, Svayrieng and Khmer Tertiary rift basins. Tonle Sap and Svayrieng Basins are interpreted to be formed by extension during the Middle Eocene – Early Oligocene and inversion, uplift and denudation during the Miocene. The Khmer Basin was formed by rifting during the Eocene to the Late Oligocene, followed by rapid thermal subsidence from the Early to Middle Miocene. Finally, Khmer basin was affected by the Middle – Late Miocene to Pleistocene inversion.